An international polypectomy practice survey. (2nd April 2020) - Willems, Philippe; Orkut, Sinan; Ditisheim, Saskia; Pohl, Heiko; Barkun, Alan; Djinbachian, Roupen; Bouin, Mickael; von Renteln, Daniel
Abstract: Background and study aims: In recent years, cold snare polypectomy (CSP) has been recommended as the preferred approach for removal of small and diminutive colorectal polyps. We conducted an international survey among endoscopists to understand the uptake of CSP and changes in polypectomy practice during recent years. Patients and methods: Endoscopists were invited through gastroenterology, colorectal surgery and endoscopy societies to participate in an online survey. The primary outcome was to identify the predominant polypectomy approach used to remove 4‒10 mm colorectal polyps. Secondary outcomes included the uptake of CSP in the past 5 years, current polypectomy practice patterns for 1‒20 mm polyps, practice changes in recent years, and perceived benefits/concerns related to different polypectomy techniques. Results: The survey was distributed internationally by nine societies and completed by 808 endoscopists (response rate 3.7%). CSP was the predominant polypectomy technique for 4‒5 mm polyps (67.0%, 95% CI, 63.7–70.2%) and 6‒10 mm polyps (55.2%, 95% CI, 51.8–58.6%). For 1‒3 mm polyps, cold forceps remained the predominant technique (78.4%, 95% CI, 75.6–81.3%), whereas hot snare polypectomy (HSP) remained the predominant technique for 10‒20 mm polyps (92.5%, 95% CI, 90.7–94.3%). 87.5% (95% CI, 85.2–89.8%) of endoscopists reported an increase in CSP use during the past 5 years. Conclusions: This survey found a substantial increase in CSP use during recent years. CSP has become the predominant polypectomy approach for 4‒10 mm colorectal polyps, while HSP remained the predominant approach for larger (10‒20 mm) polyps. Clinical practice patterns are well aligned with recently issued guideline recommendations.